Chemometric characterization of virgin olive oils of the two major Cypriot cultivars based on their fatty acid composition - Kritioti, Angelina; Menexes, Georgios; Drouza, Chryssoula (My University, 2018)
The effects of the geographical region and the botanical origin of olive oils on the profile of fatty acids isolated from monovarietal virgin olive oils from Cyprus were investigated, in order to establish, for the first time, promising models for authentication and classification of monovarietal virgin olive oils produced on the island. The two dominant Cypriot olive cultivars, Cypriot (ladoelia), and Koroneiki (lianolia), were analyzed for fatty acid composition by GC/FID after preparation of Fatty Acid Methyl Esters from olive oil, using a cold esterification method. The data obtained were analyzed statistically using multivariate and univariate ANOVA, principal components analysis (PCA) and hierarchical cluster analysis. Results showed that the olive oils can be separated into two distinct groups using the FAME data bank obtained from 225 samples. Significant differences in the proportion of some variables such as polyunsaturated linoleic acid, and the ratio C18:1/C18:2 from oils of different varieties and geographical regions were detected. The ratios C18:1/C18:2 and MUFA/PUFA, as well SFA, ω-9 and PUFA showed the higher discriminant power based on the cultivar.
Keywords: Altitude; Chemometrics; Cypriot virgin olive oil; FAME; GC-FID; GC–MS; Microclimate; Variety